Determinants of Productivity Differences in International Manufacturing - Mefford, Robert N. (Journal of International Business Studies, 1986)
To access the influence of various factors on labor productivity, a production function model of a plant in a labor-intensive consumer goods industry is developed and estimated econometrically. The model is derived from a production function specified in three functional forms which is expanded to include management and quality-adjustment factors for the capital and labor inputs. The management variable is a performance ranking of the plants in terms of meeting output, quality, and cost goals. Data on approximately 30 plants from a dozen countries over the period 1975 through 1982 was used for the analysis. All of the plants are of a single multinational firm and produce similar products.